Evaluation of the GENE-UP® Listeria spp. Method for the Detection of Listeria Species in a Variety of Foods and Select Environmental Surfaces: Collaborative Study, First Action 2019.10. (9th September 2020) - Johnson, Ronald; Mills, John; Pittet, Jean-Louis; Mathia, Olivier; Bird, Patrick; Nelson, Maria
Abstract: Background: The GENE-UP ® Listeria spp. 2 (LIS 2) assay ( Performance Tested Method SM 121803) is a real-time PCR molecular detection method for the rapid detection of Listeria species ( Listeria monocytogenes, L. innocua, L. ivanovii, L. seeligeri, and L. welshimeri ) in a variety of foods and environmental surfaces. Objective: The purpose of this validation was to evaluate the method's interlaboratory performance and submit the results to AOAC INTERNATIONAL for adoption as First Action Official Method SM for the detection of Listeria species in a variety of foods and select environmental surfaces. Method: The GENE-UP method was evaluated in a multi-laboratory study as part of the AFNOR NF VALIDATION certification process using unpaired test portions for one food matrix, full-cream goat milk cottage cheese (8.4% fat). The candidate method was compared to the ISO 11290–1/Amd.1 reference method. Sixteen participants from 15 laboratories throughout the European Union participated. Three levels of contamination were evaluated: a non-inoculated control level (0 CFU/test portion), a low contamination level (∼2 CFU/test portion), and a high contamination level (∼10 CFU/test portion). Data from that study were analyzed according to the probability of detection (POD) statistical model. Results: The dLPODC values with 95% confidence intervals between the candidate and reference method results were −0.02 (−0.07, 0.03), −0.08 (−0.31, 0.16), and 0.00 (−0.03, 0.03) for the non-inoculated, low, and high contamination levels, respectively. Conclusions: The dLPODC results demonstrate no difference in performance between the candidate method and reference method for the matrix evaluated. Highlights: Data from a singular collaborative study was used to achieve adoption as an AOAC First Action Official Method for the detection of Listeria species in a variety of foods and select environmental surfaces.